Comparative Typology in Six European Lowâ€Intensity Systems of Grassland Management (Advances in Agronomy, 2007)
management with varying degrees of arrangements in different European countries and landscapes. These large-scale grazing systems (LSGS) are rein- deer husbandry in Northern Sapmi (Fennoscandia), sheep grazing in the Polish Tatra mountains, cattle grazing in the Swiss and German Alps, cattle, sheep, and pig grazing in Baixo Alentejo, Southern Portugal, and sedentary sheep grazing in Central Spain. These systems showed very heterogeneous organizational patterns in their way of exploiting the pastoral resources. At the same time, these LSGS showed at least some of the following weaknesses such as poor economic performance, social fragility, and structural shortcomings for proper grazing management. Lack of proper mobility of herds/flocks or accession to specific grazing grounds can be a cause of environmental hazards. The sur- veyed LSGS are mostly dependent on public handouts for survival, but succes- sive policy schemes have only showed mixed effects and, in particular study areas, clear inconsistencies in their aim to stop the general declining trend of LSGS. This research assumed that detailed system research may open the way for better-focused policy intervention, but policymakers need to take advantage of this period of support to push ahead for reforms. Recent European Union (EU) guidelines (2007–2013) on Rural Development Policy (RDP) and its operative scale of high nature value (HNV) farmland can easily fit the structure and functions of low-input grazing systems and LSGS.